2021
DOI: 10.3389/fbioe.2021.680769
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Cervical Artificial Disc Replacement Using Cervical Subtotal Discectomy Prosthesis

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) sacrifices segmental mobility, which can lead to the acceleration of adjacent segment degeneration. The challenge has promoted cervical artificial disc replacement (CADR) as a substitute for ACDF. However, CADR has revealed a series of new issues that are not found in ACDF, such as hypermobility, subsidence, and wear phenomenon. This study designed a cervical subtotal discectomy prosthesis (CSDP) consisting of a cervical disc prosthesis structure (CDP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The Von Mises stress is widely used in FE study to evaluate the orthopedic implant design and risks for subsidence and implant failure ( Yu et al, 2016 ; Zhang et al, 2016 ; Liu et al, 2020 ; Wo et al, 2021 ). Besides, the stress distribution on the surface of the implant may reflect the load transfer of different implants and biomechanical environments ( Yu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Von Mises stress is widely used in FE study to evaluate the orthopedic implant design and risks for subsidence and implant failure ( Yu et al, 2016 ; Zhang et al, 2016 ; Liu et al, 2020 ; Wo et al, 2021 ). Besides, the stress distribution on the surface of the implant may reflect the load transfer of different implants and biomechanical environments ( Yu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contact method between facet cartilages was modeled as frictional contact, with the surface-to-surface method. Additionally, the friction coefficient was 0.1 ( Wong et al, 2020 ; Wo et al, 2021 ). The contact between UJs and cortical bone was identical to facet cartilages.…”
Section: Methodsmentioning
confidence: 99%
“…The vertebral body was simulated by four-node tetrahedral elements, and the rest of the material was simulated by eight-node hexahedral elements. The detailed material properties ( Lee et al, 2011 ; Cai et al, 2020a ; Guan et al, 2020 ; Hua et al, 2020 ; Ke et al, 2020 ; Wang et al, 2020 ; Sang et al, 2021 ; Wo et al, 2021 ) of all parts are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous research on CSDP finite element analysis ( Wo et al, 2021 ), we found that force can be well-transmitted without excessive stress concentration from the prosthesis to the lower bone cortex through the connection structure and CVF structure. Meanwhile, the facet joint can maintain a stable load in motion and reduce the compensatory movement demand of the adjacent segment.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that reducing the removal of one endplate reduces the risk of prosthesis subsidence; however, it may weaken the overall stability of the cervical spine sequence. In our previous research (Wo et al, 2021), we preliminarily proved by finite element analysis that the CSDP had excellent mechanical stability. However, there are limitations to the computer simulation verification.…”
Section: Introductionmentioning
confidence: 99%